A Daily Process Examination of the Bidirectional Relationship Between Craving and Alcohol Consumption as Measured Via Interactive Voice Response. (24th July 2013) - Fazzino, Tera L.; Harder, Valerie S.; Rose, Gail L.; Helzer, John E.
<x xml:space="preserve">Abstract</x> Background Craving is a central component to alcohol use disorders, although there are contradictory findings in the literature regarding the importance of craving in alcohol use. The study goal was to examine the bidirectional relationship between craving and alcohol consumption in heavy drinkers. Methods Participants received brief alcohol interventions from their primary care physicians and then were asked to make daily reports of craving and alcohol consumption to an interactive voice response (IVR) telephone system for 180 days. The study sample included 246 participants (166 men) with mean age of 46. Ninety‐seven percent were Caucasian and 66% met criteria for alcohol dependence. Analysis used generalized estimating equations (GEE) to evaluate whether craving intensity predicted next day alcohol consumption and whether alcohol consumption predicted next day craving intensity. Significant interactions with gender led to stratified analyses. Results GEE analyses revealed a significant bidirectional relationship between craving and drinking, where craving intensity predicted next day total drinks consumed (p = 0.001), and total drinks predicted next day craving intensity (p = 0.02). Exploratory analysis found that gender significantly moderated the craving–drinking relationship (p = 0.002) with men increasing next day alcohol use more (b = 0.19) than women (b = 0.08). Conclusions Findings suggest a bidirectional relationship between craving and drinking may contribute to the development or maintenance of heavy drinking, particularly for men. Based on our findings, we recommend that during brief interventions, physicians address both drinking and craving and provide advice for coping with craving.